Mashlaha in Financing Risk Measurement in Sharia Financing Institutions - Said, Salmah; Sofyan, A. Syathir; Amiruddin, Andi Muhammad Ali (Ekonomi Syariah IAIN Kudus, 2019)
The crisis of confidence in the credit rating agency forced Islamic financing institutions to apply risk measurement methods independently and renewed the study of credit risk measurement. Moreover, this research also discusses mashlaha (public interest) in measuring financing risk. This research uses a mixed method approach, combining quantitative methods to measure risk by utilizing CreditRisk+, and qualitative methods in analyzing mashlaha in these measurements. This study revealed that CreditRisk+ is able to measure financing risk accurately. This study also found that there is mashlaha as part of maqashid al-sharia in risk measurement, namely 1) Tahdzib al-Fard, that makes a financial institution capable of independently measuring the risk of its own financing; 2) Iqamah al-Adl, independent measurement will create information justice by comparing measurement results both internally and externally. 3) Mashlaha itself, with internal risk measurement, will reduce systemic risk. The implications of this study is the use of mashlaha in analyzing financing risk provides more stringent prudential in the measurement of financing risk.